Economic and Legal Aspects of Tourism Regulation in the New Economy: International Practice - SAFAEVA, Sayyora Rikhsibaevna; ISHANKHODJAEVA, Dildora Aleksandrovna; JURAEVA, Nargiza Abduvohidovna; MATYUNINA, Olga Evgenievna (Journal of Environmental Management and Tourism, 2019)
The article is concerned with measures to be taken to systematize the economic and legal aspects of tourism regulation in the new economy. International experience of government regulation in the tourism sector in the new economy shows that it makes sense to use separate components of government regulation mechanisms to develop the tourism industry in Russia taking into account its historical, cultural and natural potential. The European model has been proved as the most optimal as it suggests the formation of marketing divisions that will forge and promote a national tourist product, conduct marketing research, carry out advertising activities, arrange and hold international tourism exhibitions, conferences and seminars. The tourism sector as a multi-industry complex is established to be in need of coordination for its economic activities. Excessive government presence and regulation are determined to dampen entrepreneurial initiatives, which are the basis for the establishment and development of market relations in the tourism industry.